A critical review with solar radiation analysis model on inclined and horizontal surfaces - Balo, Figen; Sua, Lutfu S. (Inst Engineering Tech-Iet, 2019)
Utilization of renewable energy resources is gradually increasing in developing countries as well as the developed ones. Although the use of these resources is becoming increasingly important to meet energy demands, efficient use of limited resources requires planning and in-depth analysis beforehand. Correspondingly, in recent years, countries have started to work on increasing the share of renewable energy among other energy-production methods to ensure energy independence. In this study, in order to design PV system for maximum efficiency under certain climatic conditions, a comparative analysis of solar energy potential for two cities in certain climatic conditions is conducted. Based on the calculations, the values of the indicators show that potential for photovoltaic systems in both cities correspond to expected levels. The study aims to determine the most efficient solar panel by utilizing the real solar radiation values obtained for the photovoltaic system design.
Keywords: Artificial Neural-Network; Sunshine Duration; Empirical-Models; Prediction; Formula; Cities; Region; Ann